Membranous Nephropathy Associated With Immunological Disorder-Related Liver Disease. Issue 30 (July 2015) - Dauvergne, Maxime; Moktefi, Anissa; Rabant, Marion; Vigneau, Cécile; Kofman, Tomek; Burtey, Stephane; Corpechot, Christophe; Stehlé, Thomas; Desvaux, Dominique; Rioux-Leclercq, Nathalie; Rouvier, Philippe; Knebelmann, Bertrand; et al.
<x xml:space="preserve">Abstract</x> Abstract The association between membranous nephropathy (MN) and immunological disorder-related liver disease has not been extensively investigated, and the specific features of this uncommon association, if any, remain to be determined. We retrospectively identified 10 patients with this association. We aimed to describe the clinical, biological, and pathological characteristics of these patients and their therapeutic management. The possible involvement of the phospholipase A2 receptor (PLA2R) in these apparent secondary forms of MN was assessed by immunohistochemistry with renal and liver biopsy specimens. The mean delay between MN and liver disease diagnoses was 3.9 years and the interval between the diagnosis of the glomerular and liver diseases was <1.5 years in 5 patients. MN was associated with a broad spectrum of liver diseases including primary biliary cirrhosis (PBC), autoimmune hepatitis (AIH), and primary sclerosing cholangitis (PSC). AIH whether isolated (n = 3) or associated with PBC (n = 2) or PSC (n = 2) was the most frequent autoimmune liver disease. Circulating PLA2R antibodies were detected in 4 out of 9 patients but the test was performed under specific immunosuppressive treatment in 3 out of 9 patients. Seven of the 9 patients with available renal tissue specimens displayed enhanced expression of PLA2R in glomeruli whereas PLA2R was not expressed in liver parenchyma from these patients or in normal liver tissue. The study of immunoglobulin (Ig) subclasses of deposits in glomeruli revealed that the most frequent pattern was the coexistence of IgG1 and IgG4 immune deposits with IgG4 predominating. Detection of PLA2R antibodies in glomeruli but not in liver parenchyma is a common finding in patients with MN associated with autoimmune liver disease, suggesting that these autoantibodies are not exclusively detected in idiopathic MN.